PENERAPAN STRATEGI LSQ BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI - Fakhratus, Sholikhah (Economic Education Analysis Journal, 2012)
The process which is being a constraint at High School 1 Kroya is the activities of  students in the learning process still lacking, the students still feel scared and ashamed to ask if  there isn’t  an  encouragement from the teacher, the teacher is still lack in the development of  teach-ing variation. The above is caused of   needing to the use of  appropriate and varied methods and media as a tool in teaching and learning, one of  the alternatives by applying the learning strategies Learning Start With A Question (LSQ) assisted by audio visual media. The design of  this study is an action research class with two cycles, each cycle includes planning, imple-mentation, observation and reflection. The results on the cycle I shows the average of   student learning outcomes is 71,5 with classical completeness 65.7%, 67.71% of  the student activity in the high category, teacher’s activity in the learning is 67.5% or high category. For the result on the cycle II showed an average of  student learning outcomes 78,6 with classical complete-ness 85.7%, 76.57% of  student activities or activities of  the students in the high category, for teachers’ activity is 87.5% with very high criteria.